PENGARUH PENGGUNAAN MEDIA SCRATCH BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR SISWA PADA MATERI SUDUT DI KELAS V SD NEGERI 50 BANDA ACEH - Putri Balqis; Linda Vitoria; Suci Fitriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of local wisdom–based Scratch media on students’ learning outcomes in angle material at the elementary level. A quantitative approach with a quasi-experimental posttest-only control group design was employed. The participants consisted of 57 fifth-grade students divided into experimental and control groups. An essay test was used to measure learning outcomes. Since the data were not normally distributed, the Mann–Whitney U test was applied. The results revealed a significant difference between the two groups with a significance value of 0.015 (<0.05). The mean score of the experimental group (75.17) was higher than that of the control group (60.00). These findings indicate that integrating Scratch media with local cultural elements effectively enhances students’ conceptual understanding of angles in elementary mathematics learning.